MIX Design Beton Metode SKSNI dan ACI dengan Bantuan Bahasa Pemrograman Komputer - Widi Hartono (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
This paper presented computer programming of concrete mix design used Microsoft®Visual Basic™: NCMD. The procedures use by this computer program are based on SKSNIand ACI method of concrete mix design. The method was developed for use with cement,aggregates, and water, which conform to the relevant Indonesian and American standard.However since this standards lay down requirements which materials must meet in order tobe suitable for good quality concrete, the procedures of SKSNI and ACI method can beapplied to concrete mix design generally. The object of this computer program is to find theproprotions in which the concrete material - cement, water, fine aggregate, and coarseaggregate - should be combined in order to provide the specified strength, workability,durability, and possibly meet other requirements, as listed in standard such the SKSNI andACI standard.Keywords: mix design, concrete, computer programming, visual basic™.